A Monoclonal Antibody against a peptide sequence of Fibrinogen Gamma Chain Acts as an Inhibitor of factor XIII-Mediated Crosslinking of Human Fibrin - Taubenfeld, stephen M; Song, Yeqing; Sheng, DeQuan; Ball, Evelyn L; Matsueda, R Gary (Thrombosis and Haemostasis, 1995)
Recurrent hemorrhage has been reported in humans as a result of acquired antibody inhibitors which interfere with the crosslinking of fibrin by factor XIII. One type of these inhibitors (Type III) prevents activated factor XIII from acting on fibrin. We have generated an anti- fibrin monoclonal antibody, called mAb 4A5, which binds to a peptide sequence at the carboxyl-terminus of human fibrinogen γ-chains. MAb 4A5 acts like a Type III inhibitor and prevents proper factor XHI-mediated crosslinking. Pre-incubation of fibrinogen or pooled human plasma with mAb 4A5, but not mAb D2 (specific for the carboxyl terminus of fibrin α-chains), resulted in clots which are soluble in either 5 M urea or 1% monochloroacetic acid. SDS-PAGE and immunoblotting analysis of these clots confirmed that mAb 4A5 inhibited γ-chain crosslinking in plasma clots and fibrin clots. Results from a factor XIII activity assay demonstrated that biotinylcadaverine cross-linking into fibrin by factor XIII could be inhibited by mAb 4A5 but not mAb D2, arguing that mAb 4A5 acted by binding the crosslinking site of factor XIII. Studies of the immunoreactivity of these mAbs with 12 different animal species showed that the γ-chain epitope recognized by mAb 4A5 was more conserved than the α-chain epitope recognized by mAb D2. The species fibrinogens, recognized by mAb 4A5 in binding assays, also showed impaired crosslinking when mAb 4A5 was present during the clotting reaction.